Studi Pengaruh Penambahan Bahan Additive TX-300 Terhadap Kuat Tekan Batu Bata Pasca Pembakaran - Bintang, Alhadi Pratama; Setyanto, Setyanto; Adha, Idharmahadi (Universitas Lampung, 2015)
Along with the rise of civil construction such as housing or settlements, also increase the demandfor bricks. To be able to meet the needs of these bricks, brick production must be increased. Notonly an increase in production should be done, but the increase in terms of quantity and in termsof quality also needs to be done. One way to do is to add an additional mixture to the compositionof the brickyardIn this study used clay and additional materials TX-300 which has a variety of levels of 0.6 ml, 0.9ml, 1.2 ml and 1.5 ml with the purpose to improving the quality of the bricks, as well as comparingstrong press bricks by modifying the combustion time. Soil samples tested in this study is claywhich derived from Nyunyai street, Rajabasa, Bandar Lampung. Variations of burning time is usedfor one day, two days and three days.After doing research, from the fourth level, the compressive strength maximum average post-combustion bricks are at a level of 1.5 ml with a burning for two days. The compressive strengthvalue of 46.01 kg / cm2. This is due to the greater levels of TX-300, the greater the compressivestrength value, besides the most optimum burning time is for 2 days, this was due to theevaporation of water contained in the most optimum bricks are burning for two days.Keywords: Bricks, Clay, TX-300, Compressive Strenght